Targeting the NPY/NPY1R signaling axis in mutant p53–dependent pancreatic cancer impairs metastasis - Chambers, Cecilia R.; Watakul, Supitchaya; Schofield, Peter; Howell, Anna E.; Zhu, Jessie; Tran, Alice M. H.; Kuepper, Nadia; Reed, Daniel A.; Murphy, Kendelle J.; Channon, Lily M.; Pereira, Brooke A.; Tyma, Victoria M.; et al. (Science advances, 2025)
Pancreatic cancer (PC) is a highly metastatic malignancy. More than 80% of patients with PC present with advanced-stage disease, preventing potentially curative surgery. The neuropeptide Y (NPY) system, best known for its role in controlling energy homeostasis, has also been shown to promote tumorigenesis in a range of cancer types, but its role in PC has yet to be explored. We show that expression of NPY and NPY1R are up-regulated in mouse PC models and human patients with PC. Moreover, using the genetically engineered, autochthonous KP R172H C mouse model of PC, we demonstrate that pancreas-specific and whole-body knockout of Npy1r significantly decreases metastasis to the liver. We identify that treatment with the NPY1R antagonist BIBO3304 significantly reduces KP R172H C migratory capacity on cell-derived matrices. Pharmacological NPY1R inhibition in an intrasplenic model of PC metastasis recapitulated the results of our genetic studies, with BIBO3304 significantly decreasing liver metastasis. Together, our results reveal that NPY/NPY1R signaling is a previously unidentified antimetastatic target in PC. Targeting NPY1R reduces mutant p53–dependent pancreatic cancer metastasis.